Legal Regulations against Children Committing the Crime of Murder - Wijanto Hadi Kasturi; Erny Herlin Setyorini; Otto Yudianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to examine how Legal Regulations against Children Committing the Crime of Murder. The type of research method used in this research is normative juridical. The result shows that the legal arrangements for children who commit the crime of murder are very clearly regulated in the Law of the Republic of Indonesia Number 35 of 2014 concerning Amendments to Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection where for 2 (two) children in conflict with the law have been snared in Article 76C in conjunction with Article 80 paragraph (3). In addition, the examination of cases conducted by law enforcement officers, especially judges and public prosecutors, uses case examination using the Juvenile Criminal Justice System as regulated in Law Number 11 of 2011 concerning the Juvenile Justice System.